Nivolumab plus cabozantinib versus sunitinib in first-line treatment for advanced renal cell carcinoma (CheckMate 9ER): long-term follow-up results from an open-label, randomised, phase 3 trial. Issue 7 (July 2022) - Motzer, Robert J; Powles, Thomas; Burotto, Mauricio; Escudier, Bernard; Bourlon, Maria T; Shah, Amishi Y; Suárez, Cristina; Hamzaj, Alketa; Porta, Camillo; Hocking, Christopher M; Kessler, Elizabeth R; Gurney, Howard; et al.
Summary: Background: In the primary analysis of CheckMate 9ER, nivolumab plus cabozantinib showed superior progression-free survival, overall survival, and objective response over sunitinib in patients with previously untreated advanced renal cell carcinoma (median follow-up of 18·1 months). Here, we report extended follow-up of overall survival and updated efficacy and safety. Methods: This open-label, randomised, phase 3 trial was done in 125 hospitals and cancer centres across 18 countries. We included patients aged 18 years or older with previously untreated advanced or metastatic clear-cell renal cell carcinoma, a Karnofsky performance status of 70% or higher, measurable disease according to Response Evaluation Criteria in Solid Tumors version 1.1 assessed by the investigator, any International Metastatic Renal Cell Carcinoma Database Consortium (IMDC) prognostic risk category, and available tumour tissue for PD-L1 testing. Patients were randomly assigned (1:1) to nivolumab (240 mg) intravenously every 2 weeks plus cabozantinib (40 mg) orally once daily or sunitinib (50 mg orally) once daily (4 weeks per 6-week cycle). Randomisation, stratified by IMDC risk status, tumour PD-L1 expression, and geographical region, was done by permuted block within each stratum using a block size of four, via an interactive response system. The primary endpoint was progression-free survival by blinded independent central review. Overall survival was a secondary endpoint (reported here as the preplanned final analysis according to the protocol). Efficacy was assessed in all randomly assigned patients; safety was assessed in all patients who received at least one dose of any study drug. This ongoing study, closed to recruitment, is registered with ClinicalTrials.gov, NCT03141177 . Findings: Between Sept 11, 2017, and May 14, 2019, 323 patients were randomly assigned to the nivolumab plus cabozantinib group and 328 to the sunitinib group. With an extended follow-up (data cutoff of June 24, 2021; median 32·9 months [IQR 30·4–35·9]), median overall survival was 37·7 months (95% CI 35·5–not estimable) in the nivolumab plus cabozantinib group and 34·3 months (29·0–not estimable) in the sunitinib group (hazard ratio [HR] 0·70 [95% CI 0·55–0·90], p=0·0043) and updated median progression-free survival was 16·6 months (12·8–19·8) versus 8·3 months (7·0–9·7; HR 0·56 [95% CI 0·46−0·68], p<0·0001). Grade 3–4 treatment-related adverse events occurred in 208 (65%) of 320 patients with nivolumab plus cabozantinib versus 172 (54%) of 320 with sunitinib. The most common grade 3–4 treatment-related adverse events were hypertension (40 [13%] of 320 patients in the nivolumab plus cabozantinib group vs 39 [12%] of 320 in the sunitinib group), palmar–plantar erythrodysaesthesia (25 [8%] vs 26 [8%]), and diarrhoea (22 [7%] vs 15 [5%]). Grade 3–4 treatment-related serious adverse events occurred in 70 (22%) of 320 patients in the nivolumab plus cabozantinib group and 31 (10%) of 320 in the cabozantinib group. One additional treatment-related death occurred with sunitinib (sudden death). Interpretation: With extended follow-up and preplanned final overall survival analysis per protocol, nivolumab plus cabozantinib demonstrated improved efficacy versus sunitinib, further supporting the combination in the first-line treatment of advanced renal cell carcinoma. Funding: Bristol Myers Squibb and Ono Pharmaceutical.